P071 Intestinal CD8+ T cell exhaustion is linked to disease activity in ulcerative colitis. (21st January 2022) - Grigorian, M; Salié, H; Mayer, L S; Globig, A M; Hockenjos, B; Krimmel, L; Thimme, R; Bengsch, B; Hasselblatt, P
Abstract: Background: The immune pathogenesis of ulcerative colitis (UC) has been linked to imbalanced CD4+ T-cell responses while the contribution of CD8+ T cells is less well characterized. Chronically activated CD8+ T cells may become dysfunctional and acquire an exhausted phenotype during chronic viral infection or cancer. Recently, exhausted T cell (Tex) signatures have been proposed as a potential prognostic marker in autoimmune diseases. We therefore set out to characterize features of CD8+ T cell exhaustion in UC patients in more detail. Methods: Lymphocytes were isolated from peripheral blood and sigmoid biopsies of UC patients in remission (n = 9) and active disease (n = 20). Cytokine production and expression of exhaustion-associated markers were analyzed ex vivo by flow cytometry. Results were correlated with disease activity (Mayo Score) and mucosal inflammation (assessed endoscopically and histologically [Nancy Score]). To further analyze the role of CD8+ T cells within the intestinal tissue microenvironment, Imaging Mass Cytometry (IMC) was applied on sigma biopsies (n= 21). Results: Analysis of CD8+ Tex marker expression and functionality did not reveal major differences between peripheral blood lymphocytes isolated from UC patients with either active disease or remission as well as healthy controls. In contrast, in the sigmoid colon of patients with active UC, CD8+ T cell numbers were strongly increased. Moreover, expression of exhaustion markers was significantly increased in intestinal CD8+ T cells during active disease compared to remission. These cells also displayed dysfunctional cytokine profile patterns, as assessed by an established functional exhaustion score. This phenotype also closely correlated with clinical, endoscopic and histological markers of UC disease activity. The findings were confirmed by IMC, which revealed the presence of several clusters of CD8+ T cells with an exhaustion signature in inflamed colonic tissues. Conclusion: Our findings indicate that inflammation in the intestines of UC patients is associated with the induction of CD8+ T-cell responses that phenotypically and functionally resemble Tex. The functional relevance, prognostic value and therapeutic relevance of these exhausted CD8+ T cell signatures in UC need to be analyzed in future studies.